RAGAM ANTONIM DALAM BUKU TEKS BAHASA JEPANG - Randi Triades; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to identified variety of antonyms used in the Japanese text books Minna no Nihongo Shokyuu I, II and New Approach Japanese Intermediate Course. The method is a descriptive qualitative were used the theory of variety of antonym by Fromkin and Rodman. Based on the analysis, variety of antonyms was found. That is complementary antonyms, gradable antonyms, relational antonyms, reciprocal antonyms, and hyponyms.Key Words: Antonyms, Variety of Antonyms, Japanese Text Book